망막대동맥류에 합병된 황반출혈환자에서 베바시주맙 단독 치료의 임상양상 - 김지수(Ji Soo Kim), 채주병(Ju Byung Chae), 김진영(Jin Young Kim), 형성민(Sung Min Hyung), 김동윤(Dong Yoon Kim) (Daihan angwa haghoi jabji, 2019)
목적: 망막대동맥류(retinal arterial macroaneurysm)에 합병된 황반출혈(submacular or subinternal limiting membrane hemorrhage) 환자에서 유리체강내 베바시주맙 주사 단독 치료의 임상양상을 분석하고자 한다. 대상과 방법: 망막대동맥류에 합병된 황반출혈로 유리체강내 베바시주맙 주사를 시행한 환자(17명 17안)를 대상으로 후향적 의무기록조사를 시행하였다. 유리체강내 베바시주맙 주사 치료 이후 시력개선 정도, 중심망막두께 변화 등을 분석하였다. 1 logMAR 시력을 기준으로 치료 후 시력이 좋은 군과 나쁜 군으로 나누어 비교 분석하였다. 결과: 망막대동맥류에 합병된 황반출혈로 유리체강내 베바시주맙 치료를 시행받은 환자(17명 17안)의 평균 나이는 78.47 ± 7.84세였다. 평균 경과 관찰 기간은 3.99 ± 2.99개월이었으며, 평균 베바시주맙 주사 횟수는 2.12 ± 1.36회였다. 유리체강내 베바시주맙 치료 후 의미 있는 시력호전과 중심망막두께의 감소가 있었으며, 치료 이후 시력예후가 좋은 군에서는 증상의 시작부터 치료 시작까지의 기간이 짧았다. 결론: 망막대동맥류에 합병된 황반출혈환자에서 유리체강내 베바시주맙 주사 단독 치료는 시력 개선과 중심망막두께의 감소에 있어 좋은 결과를 보였으며, 치료를 빨리 시작하여 좋은 시력예후를 보였다. Purpose: To evaluate the clinical features of intravitreal bevacizumab injection in patients with macular hemorrhage (submacular or subinternal limiting membrane hemorrhage) secondary to a retinal arterial macroaneurysm. Methods: We retrospectively reviewed the medical records of 17 eyes of 17 patients who underwent intravitreal bevacizumab injection with macular hemorrhage secondary to retinal arterial macroaneurysm. We evaluated the improvement of visual acuity and changes in central retinal thickness after intravitreal injections of bevacizumab. According to the final visual acuity, the characteristics of the good and poor visual prognoses groups were compared. Results: The mean age of patients (17 eyes) who underwent intravitreal bevacizumab treatment for macular hemorrhage secondary to retinal arterial macroaneurysm was 78.47 ± 7.84 years. The mean follow-up period was 3.99 ± 2.99 months, and the mean number of injections of bevacizumab was 2.12 ± 1.36. There were significant improvements in visual acuity and central retinal thickness, and the duration from symptom onset to treatment was shorter in patients with good visual prognoses. Conclusions: Intravitreal bevacizumab injection alone was effective for improving visual acuity and decreasing central retinal thickness in patients with macular hemorrhage secondary to retinal arterial macroaneurysms. KCI Citation Count: 0